(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The recent death of Giorgio Chittolini, one of Italy’s leading medievalists, provides an opportunity for a personal remembrance and a brief reflection on his scholarly personality, also in light of his latest collection of essays on ecclesiastical institutions.